PENGARUH APLIKASI BERBASIS ANDROID TENTANG PERSIAPAN PERSALINAN TERHADAP PENGETAHUAN DAN SIKAP IBU HAMIL TRIMESTER III DI WILAYAH KERJA PUSKESMAS OPHIR KABUPATEN PASAMAN BARAT - Oktavia, Sesmi Nanda; Oktavia, Try Maya (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Abstract : Childbirth preparation is everything that is prepared to welcome the birth of a child by a pregnant woman. Mobile phone applications have made it easy to provide education. Health education can be carried out using an Android application regarding childbirth preparation to increase the knowledge and attitudes of third trimester pregnant women in preparing for childbirth. The research method uses a quasi experimental method with one group pre test post test. The population in this study were third trimester pregnant women. Sampling used non-probability sampling with a purposive sampling technique as many as 15 respondents from pregnant women in the third trimester. Results based on the mean difference test, there was an increase in the average knowledge score of 18.33 after being given the Android application intervention. There was an increase in the average attitude score of 16.66 after being given the Android application. The results of the paired t test showed that there was no significant difference in knowledge scores (p= 0.01) and attitudes (p= 0.01) regarding childbirth preparation in the pretest posttest after the intervention using the Android application. Conclusion: There is a difference in pretest and posttest scores on knowledge and attitudes after being given an Android application intervention regarding childbirth preparation. Suggestion: Effective Android applications are an option in providing health education and it is hoped that pregnant women can prepare well for childbirth.Keywords: Childbirth Preparation, Knowledge, Attitude, Third trimesterpregnantwomen Android-Based Applications